Transformasi Sistem Informasi Desa Berbasis Web (Studi Kasus di Kelurahan Tanjung Lombok Timur) - Saiful, Muhammad; L.M.Samsu (Fakultas Teknik Universitas Hamzanwadi, 2024)
This study aims to examine the transformation of web-based village information systems in Tanjung Village, East Lombok. The primary focus of this research is to improve data management, public service transparency, and community participation through the application of modern web technologies. The system is developed using the waterfall method, encompassing the stages of needs analysis, design, implementation, testing, and maintenance. The results of the study show significant improvements in data accuracy, information delivery speed, and citizen engagement. These findings provide a model that can be applied in other villages seeking to update their information systems to enhance public service efficiency and effectiveness.